Investigation of enclosure aspect ratio effects on melting heat transfer characteristics of metal foam/phase change material composites. Issue 9 (28th June 2019) - Samimi Behbahan, Amin; Noghrehabadi, Aminreza; Wong, C.P.; Pop, Ioan; Behbahani-Nejad, Morteza
Abstract : Purpose: The purpose of this paper is to study thermal performance of metal foam/phase change materials composite under the influence of the enclosure aspect ratios (ratio of enclosure height: length). In this study, a compound metal foam/phase change material (PCM), which has been proved to be one of the most promising approaches for thermal conductivity promotion on PCMs, was used. Design/methodology/approach: The PCM is considered initially at its melting temperature. The enclosure for all the cases has a constant volume with various aspect ratios. The left side of the enclosure is suddenly exposed to a thermal source having a constant heat flux, while the other three surfaces are kept thermally insulated. A two-dimensional numerical model considering the non-equilibrium thermal factor, non-Darcy effect and local natural convection was proposed. The coupling between velocity and pressure is solved using the SIMPLEC, and the Rhie and Chow interpolation is used to avoid the checker-board solutions for the pressure. Findings: The effects of foam porosity and aspect ratio of the enclosure on the PCM's melting time were investigated. The results indicated that enclosure aspect ratio plays a fundamental role in phase change of copper foam/PCM composites. For higher porosities, enclosures with bigger aspect ratios proved to led to optimal melting time. Besides, the best enclosure aspect ratio and foam porosity for a fixed-volume enclosure to have the shortest melting time are 2.1 and 91.66 per cent, respectively. However, for a specific amount of PCM inside a variable volume enclosure, the optimal melting time was for foam with ε = 95 per cent. The achieved results prove the great importance of selection of aspect ratio to benefit both conduction and convection heat transfer simultaneously. Originality/value: The area of energy storage systems is original.